The Implementation of Independent Learning Curriculum (Merdeka Belajar) at the Primary School Level - Suplimi Hartobi; Ahmad Suradi; Adi Saputra (Indonesian Journal of Innovative Teaching and Learning, 2024)
Background: The Independent Learning Curriculum (Merdeka Belajar) is a transformative initiative by the Indonesian Ministry of Education aimed at promoting student-centered learning, flexibility, and character development. Its successful implementation at the primary school level is crucial to achieving national education goals. Objective: This study aims to explore the implementation pattern of the Independent Learning Curriculum at SD Negeri 56 Kota Bengkulu. Method: The research employed a qualitative approach using a case study method. It was conducted at SD Negeri 56 Kota Bengkulu, with data collected through in-depth interviews. Data validity was ensured through triangulation, and analysis was carried out in three stages: data reduction, data presentation, and conclusion drawing. Results: The findings indicate that SD Negeri 56 Kota Bengkulu has implemented the Independent Learning Curriculum effectively. The implementation process includes participation in training and mentoring programs, the development of instructional tools, and regular evaluation of curriculum execution. Conclusion: The school has demonstrated a structured and proactive approach in applying the Independent Learning Curriculum, showing positive steps toward embracing student-centered and flexible learning models. Contribution: This study serves as a valuable reference for school leaders, teachers, and education practitioners in understanding and advancing the implementation of the Independent Learning Curriculum across primary schools.